Genome-wide association mapping for heat shock tolerance in Mercenaria mercenaria through SNP microarray analysis - Huiping Yang; Denis Grouzdev; Zhenwei Wang; Jayme C Yee; Yangqing Zeng; Leslie Sturmer; Bassem Allam (BMC Genomics)
Abstract Background The northern quahog Mercenaria mercenaria is a major aquaculture species on the US East Coast, and heat resistance is the most sought trait for aquaculture. This study aimed to establish a genome-wide association for heat tolerance using a 66K SNP array for M. mercenaria. Quahogs from three farms were combined for a heat challenge at 1 °C per day from 24 °C to 35 °C and stay for two days (Phase I), decreasing to 27 °C in 24 h, to 24 °C in another 24 h, and maintaining at 24 °C (Phase II) until no one dead within 48 h at 24 °C (Phase III). Dead and live quahogs were sampled for genotyping using the SNP array. Results During the heat challenge, different mortalities among the quahogs from the three farms were identified at 38, 46, and 55% at Phase I, and 36, 30, and 29% at Phase II. For the survivors (Phase III), no changes were found in body weight before and after the heat shock challenges (p < 0.265). The PCA analyses of SNP frequencies indicated significant genetic differences associated with quahog survival under heat stress across the different farms. The heritability of the heat tolerance was 0.680 ± 0.063. GWAS analysis indicated that one SNP exhibited a significant association with the time-to-death trait on chromosome 7 (p = 1.98 × 10− 5). More significant SNPs (p < 10− 3.5) were inside genes that have been reported to function in heat tolerance such as serine/threonine-protein kinase 31 and carbohydrate sulfotransferase 11, and some genes found within 50 K bp far from SNP sites have a relationship with heat tolerance such as toll-like receptors 4 and 6 (TLRs 4 and TLRs 6), uracil-DNA glycosylase, and a disintegrin and metalloproteinase with thrombospondin motifs gon-1 (ADAMTs). Conclusion The fastStructure analysis revealed the proportions of different ancestral components within the quahogs from different farming stocks, highlighting that the genetic factors may contribute to their varying survival rates under heat stress. The associated genes have potential roles in immune response, cellular stress, and tissue repair. The findings highlighted the power of high-throughput approaches for the identification of superior quahog genotypes for further breeding.